PERANCANGAN APLIKASI ABSENSI GURU SMKN 8 KABUPATEN TANGERANG BERBASIS WEB MENGGUNAKAN METODE EXTREME PROGRAMMING - Pandi Fillahi; Willis Puspita Sari (CV. Multi Kreasi Media, 2024)
The attendance system at SMKN 8 Tangerang Regency currently still uses paper forms. Each teacher takes attendance every time they enter and leave teaching, filling in attendance using a paper form that is made manually every day by all teachers concerned to the on-duty teacher, and is manually summarized by administrative staff and then submitted to the principal every month. This system takes a long time and requires a set of office stationery so that over time there will be an accumulation of data in the form of an accumulation of attendance paper for years. The impact of this is that the data will become obsolete and cannot be reused as a history of the teacher's discipline in the future. The creation of this application uses PHP as a programming language and MySQL as a database, while the methodology used is the extreme programming method (XP). From this study, it resulted in a web-based teacher attendance application design application for SMKN 8 Tangerang Regency using the extreme programming method (Case Study: SMKN 8 Tangerang Regency) which is expected to be able to monitor the attendance of teachers and students at SMKN 8 Tangerang Regency.